A density functional theory study of poly(vinylidene difluoride) crystalline phases. (28th September 2019) - Pelizza, Francesco; Johnston, Karen
Abstract: The structure and energetics of crystalline phases of poly(vinylidene difluoride) were investigated using density functional theory (DFT). In particular, we present data on non-polar analogues of the β and γ phases that have not yet been experimentally characterised. The results from a variety of exchange and correlation functionals were compared and it was found that van der Waals (vdW) interactions have an important effect on the calculated crystal structures. While the relative phase energies were not strongly dependent on the functional, the cohesive energies were significantly affected. Graphical abstract: Image 1 Highlights: Non-polar analogue of β phase, denoted ζ, characterised for the first time. ζ structure has coplanar chains and space group Pmma. Transition barrier from β to ζ is less than 20 kJ/mol. Our monoclinic angle for ε phase is 90 degrees, not 120 degrees as previously reported. Phase energies per monomer of all PVDF phases vary by less than around 10 kJ/mol